BIRTH PREPAREDNESS AMONG WOMEN COMING TO POF HOSPITAL WAH; A CROSS SECTIONAL STUDY - Khan, Khola Waheed; Ramzan, Musarat; Nadeem, Sadia (Journal of Ayub Medical College Abbottabad, 2019)
Background: High women deaths due to pregnancy, child birth and postpartum complications were the hallmarks of the end of last century especially in Asia. Strategy adopted to achieve this is called birth preparedness whose main aim is to empower the community. This study was planned to determine the frequency of awareness about birth preparedness and the association of birth preparedness with the educational and employment status of the women Methods: It was a cross sectional study carried out in Pakistan Ordinance Factories Hospital Wah Cantt. A sample of 385 women was calculated by WHO sample size calculator. The sample was selected by purposive sampling. The study was carried out from September 2015 to March 2016. A structured questionnaire was filled regarding awareness about birth preparedness among women after taking informed consent from each of them. Demographic characteristics were recorded. Birth preparedness awareness was assessed by questionnaire containing 10 items. The data was entered and analyzed using SPSS version 19. Pearson correlation was applied to find the association of birth preparedness with the educational and employment status of the women at p-value of 0.05. Results: In a sample of 385 women, 131 (34.1%) were prepared. Statistically significant p value of 0.000 was found between birth preparedness and educational status while a p-value of 0.153 was found between birth preparedness and employment status of the women. Conclusion: The study concluded that despite having education and availability of free medical facility the women were not aware of birth preparedness. Keywords: Birth preparedness and complication readiness; Delivery; Medical facility; Safe mother hood